Misdiagnosis of myasthenia gravis presenting with tongue and palatal weakness. Issue 8 (11th August 2018) - Marshal, Megan; Mustafa, Moneeb; Crowley, Paul; McGovern, Rory; Ahern, Emer; Ragab, Inas
Abstract: We discuss the case of an elderly male who presented with a history of dysphagia, dysphonia, palatal weakness and a sensation of tongue swelling, each symptom of varying time duration. Myasthenia gravis may have a variety of presentations that include ocular fatigability, respiratory muscle weakness and bulbar symptoms. The variety of these myasthenic syndromes can serve as a barrier to diagnosis and can often result in delayed or incorrect diagnosis. In this report, we present an atypical presentation of a relatively rare condition.